2013
DOI: 10.1158/1078-0432.ccr-13-1179
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Protects Rats Treated with Intrathecal Methotrexate from Developing Spatial Memory Deficits

Abstract: Purpose To test whether memantine can prevent methotrexate-induced cognitive deficits in a preclinical model. Experimental Design After noting that methotrexate exposure induces prolonged elevations of the glutamate analog homocysteic acid (HCA) within cerebrospinal fluid, we tested whether intrathecal injection of HCA would produce memory deficits similar to those observed after intrathecal methotrexate. We then tested whether memantine, an antagonist of the N-methyl-D-aspartate (NMDA) subclass of glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…These findings revealed that MTX induced oxidative stress in the nervous system causing brain injury. This result was also observed in previous literature which declared that (ROS) generation altered neurotransmission 68 and/or induced structural brain alterations 13 while also causing mitochondrial damage which in turn causes rapid degeneration of the cells 69 and plays an important role in pathogenesis of neurodegenerative disorders, cancer and aging [21][22][23] . In addition, 57 revealed that methotrexate induced changes in neuroinflammatory markers and cellular proliferation, along with structural changes in the corpus callosum in the brain.…”
Section: Discussionsupporting
confidence: 84%
“…These findings revealed that MTX induced oxidative stress in the nervous system causing brain injury. This result was also observed in previous literature which declared that (ROS) generation altered neurotransmission 68 and/or induced structural brain alterations 13 while also causing mitochondrial damage which in turn causes rapid degeneration of the cells 69 and plays an important role in pathogenesis of neurodegenerative disorders, cancer and aging [21][22][23] . In addition, 57 revealed that methotrexate induced changes in neuroinflammatory markers and cellular proliferation, along with structural changes in the corpus callosum in the brain.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, emerging preclinical and clinical data are identifying therapeutic interventions that might protect against specific TRTs, such as dexrazoxane to prevent cardiotoxicity [100], cholesterol lowering agents to prevent bone toxicity [101,102], and memantine to prevent neurotoxicity [103]. Clinical trials testing the efficacy of these strategies might target those children with ALL at greatest risk, as determined by their individual genetic makeup.…”
Section: Discussionmentioning
confidence: 99%
“…Results are also shown as the proportion of subjects passing and failing where passing criteria is a 55% preference score. This rationale and validation of this criterion has been detailed elsewhere (Cole et al, ; Li, Vijayanathan, Gulinello, & Cole, ; Li, Vijayanathan, Gulinello, & Cole, ). There was no significant difference in motor performance of naïve WT and DKO mice on the balance beams, negative geotaxis, and object placement assays.…”
Section: Methodsmentioning
confidence: 99%